2014
DOI: 10.1016/j.sbspro.2014.10.284
|View full text |Cite
|
Sign up to set email alerts
|

Communication Competence during the Preparation Phase of the Direct Selling Communication Activities

Abstract: In understanding the communication competence components in the direct marketing business, this study was performed. The objectuves of the paper are to identify the communication activities that represent communication competence components and the outcome of communication competence components in the Preparation Phase of the direct selling activities. Interview and observation method were employed. Acquiring knowledge related to the business and spirituality; and preparing to acquire savoirs have been demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Since direct selling is primarily a communication process, the effectiveness of the distributors' communication is the key to their success (Omar, 2018). Several recent papers on the communication methods used by distributors in recruiting, promoting, and selling products were found (Andriani & Marlina, 2019;Deviacita, 2022;Gumaran & Talde, 2021;Omar, 2014Omar, , 2017Omar, , 2018. In a consumer persuasion study, Andriani & Marlina (2019) investigate distributors' communication through the lens of the persuasive strategies theory by Beebe & Beebe (2012).…”
Section: Distributor Levelmentioning
confidence: 99%
“…Since direct selling is primarily a communication process, the effectiveness of the distributors' communication is the key to their success (Omar, 2018). Several recent papers on the communication methods used by distributors in recruiting, promoting, and selling products were found (Andriani & Marlina, 2019;Deviacita, 2022;Gumaran & Talde, 2021;Omar, 2014Omar, , 2017Omar, , 2018. In a consumer persuasion study, Andriani & Marlina (2019) investigate distributors' communication through the lens of the persuasive strategies theory by Beebe & Beebe (2012).…”
Section: Distributor Levelmentioning
confidence: 99%
“…Direct selling plays an important role in the development of entrepreneurial skills [7]. To acquire knowledge related to the business of direct selling, it was concluded that one should know the marketing plan, its products and the history of the company [8].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Equipped with an effective interpersonal listening ability, the sales representative acquires perceptions required for an adaptive selling behaviors, which is favorable for sales performance (Spiro and Weitz, 1990;Weitz et al, 1986). In fact, with a suitable communication competencies an effective interaction occurs, the salesperson can stimulate consumers' interest and persuade them to buy products and services (Omar, 2014;Omar and Mustaffa, 2012).…”
Section: Communication and Listening Skillsmentioning
confidence: 99%